The Difficulty of Reconciliation after the St James Church Attack - Mason, Garth John (Religion & theology, 2018)
This article is a comparative reading of the autobiography Child of this Soil: My Life as a Freedom Fighter by Letlapa Mphahlele and the memoir by Charl van Wyk, Shooting Back: The Right and Duty of Self-Defence. The two texts culminate in recounting of the St. James Church attack in 1993 and the two men’s subsequent reconciliatory meetings. Mphahlele ordered the attack as an APLA commander and Van Wyk was the parishioner who fired back at the APLA attackers. Of interest are the conditions of possibility for dialogue between Van Wyk and Mphahlele in the context of the national narrative of reconciliation.